استخدام نماذج السلسلة الزمنية للتنبؤ عن أسعار اسهم في سوق االسهم السعودي - أ.م.د. مهدي صالح عبدالقادر قاسم أغا; م.م. روهات زادە (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study aims at finding the optimal model of the time series to predict the share price in the Saudi stock market, so that investors can helped in making their investment decisions. The study explored and constructed a Box-Jenkins models for the autoRegressive Integrated Moving Average models (ARIMA) using historical data for the closing price of Al Rajhi Bank to find the most appropriate model Of the Saudi stock market among the tested models. After applying all the required tests and statistical tools according to the BOX-Jenkins methodology, the study found that the most appropriate model for the logarithmic data series is ARIMA (1,1,1). The results showed that the accuracy of the prediction is good during, especially for short term and decreases as the length of the period Predicted.